Community involvement in school: Social relationships in a bedroom community - Preston, Jane P. (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
<span style="line-height: 115%; font-family: "Times New Roman","serif"; color: #111111; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The purpose of this qualitative case study was to describe how community involvement in school is associated with the social relationships existing/lacking within a bedroom community. Thirty-five interviews with school council members, teachers, and community members highlighted that traditional forms of community involvement in school generate connections between educators and community members, while the proximity of the city negatively affected the community’s social cohesion. Theoretically, bonding and bridging social capital fosters trust, which enables community involvement. Implications are that traditional forms of community involvement in school are catalytic springboards for developing additional forms of community involvement in school.